An EIS based study of a Ni-MH battery prototype. Modeling and identification analysis - Castro, Elida Beatriz (2010)
Modeling and simulation of the dynamics of batteries is a useful method to improve design and predict their performance. This paper outlines the development of a simple physicochemical model to simulate the impedance response of the Ni–MH battery system. The model describes the individual electrodes as porous flooded structures where the electrochemical processes take place at the active material/electrolyte interface. The physicochemical system parameters are grouped in such a way that the derived simple model can be experimentally identifiable. Experimental electrochemical impedance spectroscopy (EIS) data, recorded with a laboratory built prototype, are used to identify the model parameters by fitting the theoretical impedance function derived from the model. An analysis of the predicted dependence of the impedance function with the battery SOC and the identifiability of different system parameters are presented.